2001
DOI: 10.1148/radiology.219.3.r01jn24712
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular Impedance and Esophageal Varices in Patients with Child-Pugh Class A Cirrhosis

Abstract: A substantial proportion of patients with Child-Pugh class A cirrhosis without ascites have increased renovascular impedance; this significantly correlates with the presence of varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
3
16
2
Order By: Relevance
“…Our results show that PV time-averaged maximum velocity and peak systolic velocity, as well as liver and modified liver vascular indices, are associated with Child-Pugh classes. Some authors also reported the relationship between some liver Doppler US parameters and Child's classes, as well as an appearance of pseudonormalisation of portal vein hemodynamic when liver cirrhosis advances [57, 912, 24, 25]. However, Child-Pugh score is not the perfect system for the assessment of degree of liver cirrhosis and it has some limitations, including the subjective interpretation of ascites and encephalopathy, and some laboratory deviations, especially prothrombin time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that PV time-averaged maximum velocity and peak systolic velocity, as well as liver and modified liver vascular indices, are associated with Child-Pugh classes. Some authors also reported the relationship between some liver Doppler US parameters and Child's classes, as well as an appearance of pseudonormalisation of portal vein hemodynamic when liver cirrhosis advances [57, 912, 24, 25]. However, Child-Pugh score is not the perfect system for the assessment of degree of liver cirrhosis and it has some limitations, including the subjective interpretation of ascites and encephalopathy, and some laboratory deviations, especially prothrombin time.…”
Section: Discussionmentioning
confidence: 99%
“…Renal vasoconstriction has been documented in several series of cirrhotic patients on the base of increased resistive index [1]. In patients with refractory ascites, as well as in subjects with serum creatinine within the normal range, increased RI seems to be correlated with a higher risk of subsequent deterioration in renal function [1, 12, 15, 17–20]. In our study in contrast to liver Doppler US parameters, all intrarenal blood flow Doppler parameters except RA peak systolic velocity show a significant association with the severity of liver cirrhosis, evaluated by both Child's and MELD scores.…”
Section: Discussionmentioning
confidence: 99%
“…More in detail, we identified three DUS parameters, i.e. SA-RI, SMA-PI and RRA-RI, potentially correlated with portal pressure (expressed by HVPG) or with portal hypertensionrelated complications, such as varices and ascites (13)(14)(15)(16)(17)(18)(19)(20). In agreement with this, the results of the present study show that a significant relationship exists between the investigated DUS parameters and portal pressure in a population of patients chronically infected by HCV at stages of fibrotic evolution ranging from F2 to F4.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the threshold value of the HVPG for the formation of varices is 10 mmHg, while (13)(14)(15)(16)(17)(18)(19)(20). Several factors may be responsible for the poor correlation between DUS parameters and severe portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes in renal blood flow in HRS have been shown in other studies. 13,20 In compensated cirrhosis and decompensated cirrhosis with non-refractory ascites, although renal arterial systole and renal perfusion may be compromised, 21 the presence of a gradient across the renal arterial vessels ensures a normal distribution of renal cortical blood flow and maintenance of GFR. In decompensated cirrhosis with refractory ascites, however, the RI of the interlobular artery in the renal cortex increases which results in cortical ischaemia, a decreased GFR, oliguresis, anuresis and, finally, azotaemia.…”
Section: Discussionmentioning
confidence: 99%